2010
DOI: 10.1111/j.1447-0756.2010.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between pre-pregnancy body mass index and socioeconomic status and impact on pregnancy outcomes in Korea

Abstract: Overweight gravidas were associated with low education status, low economic status, and adverse pregnancy, whereas low weight gain during pregnancy was associated with low education status of the gravida and her husband, preterm delivery, and SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 27 publications
2
53
0
3
Order By: Relevance
“…In another research, the rate of women who gained an amount of weight above the IOM guidelines was 43.3 %, including 29 % of women gained more than 18 kg [16]. Several studies suggested that excessive weight gain during pregnancy increased the incidence of macrosomia [17][18][19][20][21][22][23][24][25][26][27][28], while others indicated no relation between them [29][30][31]. However, there is no systematic review or metaanalysis of relevant studies.…”
Section: Introductionmentioning
confidence: 96%
“…In another research, the rate of women who gained an amount of weight above the IOM guidelines was 43.3 %, including 29 % of women gained more than 18 kg [16]. Several studies suggested that excessive weight gain during pregnancy increased the incidence of macrosomia [17][18][19][20][21][22][23][24][25][26][27][28], while others indicated no relation between them [29][30][31]. However, there is no systematic review or metaanalysis of relevant studies.…”
Section: Introductionmentioning
confidence: 96%
“…Both advanced maternal age ( > 35 years) and increased BMI are widely recognized risk factors for pregnancy induced hypertension (PIH), including preeclampsia (PE) and gestational hypertension (GH), in various ethnic groups. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, the magnitudes of these two factors for risk of PIH have not been extensively studied among pregnant Japanese women. Defining the exact risk may prove to be important at the beginning of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…But after multiple logistic regression analysis, only 4 pregnancy outcomes were left significant. They were preeclampsia, higher birth weight group, cesarean sec- [5][6][7][8][9][10]. This study also posed an interesting finding regarding neonatal length.…”
Section: Discussionmentioning
confidence: 56%
“…There were studies stating that, pregnant women with high weight gain had higher risks for preterm delivery, cesarean section, macrosomia, low Apgar score and even offspring overweight/obesity and abdominal obesity in adolescence [5][6][7][8][9][10], while inadequate weight gain increased asthma, hyperemesis and low birth weight, women with ideal weight gain had less smokers, fetal distress, cesarean delivery and preeclampsia [10,11]. Women with excessive rates of gain retained more weight overall, attained a greater postpartum body mass index (BMI) and had higher levels of subcutaneous fat and overweight [11].…”
Section: Introductionmentioning
confidence: 99%